Slovenian nursing students’ competence in research utilization, and the support they received during clinical practice - Heikkilä Asta; Kaučič Boris Miha; Filej Bojana; Salminen Leena; Katajisto Jouko; Leino-Kilpi Helena (University of Ostrava, Faculty of Medicine, 2025)
Aim: Research utilization is at the core of evidence-based practice. The aim of the study was to describe Slovenian nursing students’ competence in research utilization (attitudes, knowledge, and skills) on graduation, and the support they received in learning research utilization during clinical practice.
Design: A descriptive, cross-sectional study design.
Methods: The participants were graduating Slovenian bachelor-level nursing students (n = 220). Data were collected using the Competence in Research Utilization instrument, and analyzed statistically.
Results: Students’ attitudes to research utilization were positive, but their knowledge was rather limited. Skills were self-assessed as above moderate. The majority of the students had received support in learning research utilization during their most recent clinical practice period. The support received was related to students’ attitudes and skills.
Conclusion: Educational institutions should pay attention to improving nursing students’ competence in research utilization, especially regarding their knowledge. Further research is needed to explore the most effective pedagogical strategies, including clinical practice, to improve students’ competence in research utilization and to gain a better understanding of multidimensional research utilization competence assessment.